CUSTOM-MADE RHEOMETER FOR THE EXPERIMENTAL STUDY OF POLYURETHANE RESIN PU9010 - Luciano Fissore; Stefan Diebels (Acta Polytechnica CTU Proceedings)
Polyurethane resins are well-known examples in aerospace industry, electronics and automotive as an adhesive or coating because of their broad spectrum of properties. They are obtained by a process called curing, where in the initial uncured state the mixture of monomers exhibits a viscous behavior and at the end of the polymerization reaction, a solid with viscoelastic properties is formed. The shrinkage due to cross-linking and thermal expansion cause the generation of residual stresses which often result in broken adhesive layers. Therefore, the reduction of such problems is of utmost importance. In this study, a rheometer capable to conduct oscillatory-strain-controlled experiments was built in order to apply large deformations not only to the sample at the beginning of the reaction but also during the curing process and to the fully cured adhesive.